Polybenzimidazoles based on 3,3 `-diaminobenzidine and aliphatic dicarboxylic acids: synthesis and evaluation of physicochemical properties toward their applicability as proton exchange and gas separation membrane material - Bhavsar, Rupesh S.; Nahire, Sandip B.; Kale, Mrunali S.; Patil, Shubhangi G.; Aher, Pradnya P.; Bhavsar, Ritesh A.; Kharul, Ulhas K. (Journal of Applied Polymer Science, 2011)
A series of aromatic-aliphatic polybenzimidazoles (PBIs) based on 3,3'-diaminobenzidine (DAB) and aliphatic dicarboxylic acid with incremental -CH2- groups were synthesized. Optimization of synthesis parameters and evaluation of physicochemical properties are requisite for PBI applicability as the proton exchange membrane (PEM) and gas separation membrane materials are reported. It was found that though all these PBIs exhibited high thermal, mechanical, and oxidative stability, effect of added flexibility on physical properties is not monotonous. Membranes were prepared by solution casting as well as phase-inversion method. The later types of membranes exhibited much higher H3PO4 content than its doping achieved in the solution casted membranes. These PBIs possess low hydrogen and helium permeability than that of conventional PBI. This low permeability, along with their excellent oxidative stability indicated that they can be promising PEM materials. Their CO2-sorption analysis revealed that PBI6 based on suberic acid possesses appreciable CO2 sorption. (C) 2010 Wiley Periodicals, Inc. J Appl Polym Sci 120: 1090-1099, 2011
Keywords: Gas permeation; mechanical properties; membranes; oxidative stability; polybenzimidazoles